HOW DOES MONEY FUNCTION IN THE VIEW OF ISLAMIC ECONOMICS? - Hermawan Adinugraha, Hendri (PROFJES: Profetik Jurnal Ekonomi Syariah, 2024)
This research intends to explain money’s function from the perspective of Islamic economics. This research uses a qualitative method with a library research approach sourced from books and journals that are directly or indirectly related to the function of money in the perspective of Islamic economics. The findings of this study led to the conclusion that Islamic economics views money as money, not as a commodity; money in Islam should not be stacked but must be circulated. In contrast, conventional economics views money as an unclear commodity, and traditional economics does not distinguish between money and capital. In Islamic economics, money is public goods, while mudal is private goods. Because as public goods, money should not be traded, and money functions only as a medium of exchange and not as a commodity that can be rented or traded with excess. The findings of this study confirm that Islamic economics has viewed the primary function of money as a medium of exchange and unit of account. Tracing the history of the creation of money, there are at least three fundamental objectives of the creation of currency, namely as a unit of value for the value of goods and services, as a method of storing value, and as a medium of exchange in the process of economic transactions.